2D Ruddlesden–Popper Perovskites for Optoelectronics. Issue 2 (13th October 2017) - Chen, Yani; Sun, Yong; Peng, Jiajun; Tang, Junhui; Zheng, Kaibo; Liang, Ziqi
Abstract: Conventional 3D organic–inorganic halide perovskites have recently undergone unprecedented rapid development. Yet, their inherent instabilities over moisture, light, and heat remain a crucial challenge prior to the realization of commercialization. By contrast, the emerging 2D Ruddlesden−Popper‐type perovskites have recently attracted increasing attention owing to their great environmental stability. However, the research of 2D perovskites is just in their infancy. In comparison to 3D analogues, they are natural quantum wells with a much larger exciton binding energy. Moreover, their inner structural, dielectric, optical, and excitonic properties remain to be largely explored, limiting further applications. This review begins with an introduction to 2D perovskites, along with a detailed comparison to 3D counterparts. Then, a discussion of the organic spacer cation engineering of 2D perovskites is presented. Next, quasi‐2D perovskites that fall between 3D and 2D perovskites are reviewed and compared. The unique excitonic properties, electron–phonon coupling, and polarons of 2D perovskites are then be revealed. A range of their (opto)electronic applications is highlighted in each section. Finally, a summary is given, and the strategies toward structural design, growth control, and photophysics studies of 2D perovskites for high‐performance electronic devices are rationalized. Abstract : Recent advances in 2D organometal halide perovskites are reviewed. A comprehensive comparison between 3D and 2D perovskites is provided, including crystal structure and orientation, transport dynamics, and optoelectronic performance. Among them, organic spacer engineering and modulating physical properties of 2D perovskites are highlighted. Finally, future developments and possible strategies to the unsolved challenges are outlined.